Sistema óptico de encriptación de doble máscara de fase bajo Arquitectura 4F (2010)
ABSTRACT: Nowadays the area of optical encryption of information concentrates the efforts of many researchers in laboratories around the world, mainly because contributions presented in the last two decades have shown the reliability, versatility and applicability of such systems. One of the most successful systems, which is currently protected by several patents, is based on the use of two random phase masks and a 4f architecture. In this contribution we do a review of this optical encryption system. We present the theory and the basic procedure explaining the setups and techniques that allow its experimental implementation, and we present results obtained by computational simulations of the optical virtual system to show the validity of the method.